If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6m + 13 = 9m + -2 Reorder the terms: 13 + 6m = 9m + -2 Reorder the terms: 13 + 6m = -2 + 9m Solving 13 + 6m = -2 + 9m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-9m' to each side of the equation. 13 + 6m + -9m = -2 + 9m + -9m Combine like terms: 6m + -9m = -3m 13 + -3m = -2 + 9m + -9m Combine like terms: 9m + -9m = 0 13 + -3m = -2 + 0 13 + -3m = -2 Add '-13' to each side of the equation. 13 + -13 + -3m = -2 + -13 Combine like terms: 13 + -13 = 0 0 + -3m = -2 + -13 -3m = -2 + -13 Combine like terms: -2 + -13 = -15 -3m = -15 Divide each side by '-3'. m = 5 Simplifying m = 5
| 4/5-2=10 | | 180/60b=1200 | | r-1.1=0.3 | | 18=29+a | | x/2=x+5/3 | | .7x+.3y=35 | | (3)(-3)= | | 21*10/3/x=113 | | 9v-45=6(v-6) | | (5)(5)= | | 6c-15=2c+45 | | -2(6-3x)=18 | | 35*3+x=23 | | 25w^2-1/49 | | 3x-4+5x+5=180 | | 20-16-3+1= | | 6m+19=9m-2 | | (3)(3)= | | 56=17p-23 | | 3x-8+3x=-80 | | 10=3x-115/8 | | 6v^2+v-35=0 | | 100-63= | | 34x-10=-126 | | (5x+48)=180 | | 4(z-5)=36 | | -p^2+5p+14=0 | | (x+1)(x-3)/(x+1)(x-1)*(5x-5)/(x-3)(x-1) | | 0-(-19)= | | -5(-2x-6)=18 | | 0.33(12-24v)=-2(4v-2) | | q+(7/q)=-8 |